Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (x.7 + 8) : 5 = 10
x.7 + 8 = 10.5
x.7 + 8 = 50
x.7 = 50 - 8
x.7 = 42
x = 42 : 7
x = 6
b) (x + 5).19 : 13 = 57
(x + 5).19 = 57 . 13
(x + 5).19 = 741
x + 5 = 741 : 19
x + 5 = 39
x = 39 - 5
x = 34
c) 4.(36 - 4.x) = 64
36 - 4x = 64 : 4
36 - 4x = 16
4x = 36 - 16
4x = 20
x = 20 : 4
x = 5
d) 7,6 : 19 . x = 3,2
0,4 . x = 3,2
x = 3,2 : 0,4
x = 8
e) (x : 2 + 50) : 5 = 12
x : 2 + 50 = 12 . 5
x : 2 + 50 = 60
x : 2 = 60 - 50
x : 2 = 10
x = 10 . 2
x = 20
g) 280 : (17 + 3.x) = 4
17 + 3x = 280 : 4
17 + 3x = 70
3x = 70 - 17
3x = 53
x = 53/3
h) 6.(28 - 8.x) = 72
28 - 8x = 72 : 6
28 - 8x = 12
8x = 28 - 12
8x = 16
x = 16 : 8
x = 2
i) (x - 15) : 3 : 12 = 6
(x - 15) : 3 = 6 . 12
(x - 15) : 3 = 72
x - 15 = 72 . 3
x - 15 = 216
x = 216 + 15
x = 231
a,x-25=-43 b,35-5(x+13)=-15 c,5x+6=-19 d,51-(-12+3x)=27 e,3x+4=-23
x=(-43)+25 5(x+13)=35-(-15) 5x=-19-6 -12+3x=51-27 3x=(-23)-4
x=-18 5(x+13)=35+15 5x=(-19)+(-6) -12+3x=24 3x=(-23)+(-4)
5(x+13)=50 5x=-25 3x=24-(-12) 3x=-27
x+13=50:5 x=(-25):5=-5 3x=24+12 x=-27:3=-9
x+13=10 3x=36
x=13-10 x=36:3=12
x=3
NHỚ K CHO MÌNH NHA!!!!!!!
a.x - 25 = -43
x = -43 + 25
x = -18
b.35 - 5(x + 13) = -15
5(x + 13) = 35 - (-15)
5(x + 13) = 50
x + 13 = 50 : 5
x + 13 = 10
x = 10 - 13
x = -3
c. 5x + 6 = -19
5x = -19 - 6
5x = -25
x = -25 : 5
x = -5
d.51 - (-12 + 3x) = 27
-12 + 3x = 51 - 27
-12 + 3x = 24
3x = 24 - (-12)
3x = 36
x = 36 :3
x = 12
e. 3x +4 = -23
3x = -23 - 4
3x = -27
x = -27 : 3
x = -9
a, 10 + 2x = 45 ÷ 43
10 + 2x = 45/43
2x = 45/43 - 10
2x = -385/43
x = -385/43 ÷ 2
x = -385/86
b, 2x - 138 = 23.32
2x - 138 = 736
2x = 736 + 138
2x = 874
x = 874 ÷ 2
x = 437
c, 231 - ( x - 6 ) = 1339 ÷ 13
231 - ( x - 6 ) = 103
x - 6 = 231 - 103
x - 6 = 128
x = 128 + 6
x = 134
d, x + 5.2 - ( 32 + 16.3 ÷ 6 - 15 ) = 0
x + 10 - 25 = 0
x + 10 = 0 + 25
x + 10 = 25
x = 25 - 10
x = 15
a) 10 + 2 . x = 45 : 43
2 . x = 45/43 -10
2 . x = -385/43
x = -385/43 : 2
x = -385/86
b) 2 . x - 138 = 23 . 32
2 . x - 138 = 736
2 . x = 736+138
2 . x = 874
x = 874 : 2
x = 437
c) 231 - (x -6) = 1339 : 13
231 - (x -6) = 103
x - 6 = 231 -103
x - 6 = 98
x = 98 +6
x = 104
d) x + 5 . 2 - (32 +16 . 3 : 6 - 15) = 0
x + 5 . 2 - (32 + 48 : 6 - 15) = 0
x + 5 . 2 - (32 + 8 - 15) = 0
x + 5 . 2 - 25 = 0
x + 10 - 25 = 0
x + 10 = 0 + 25
x + 10 = 25
x = 25 - 10
x = 15
a) => y+42+2y= -12-14+2y
y+2y-2y = -12-14-42
y= -68
b) => 15+y-5-5y= -12-5y
y-5y+5y= -12-15+5
y = -22
c) => 2y+5-8y+21= -3-5y-2
2y-8y+5y= -3-2-5-21
-y= -31=>y=31
d)=> -13+3y+23= -120+y
3y-y= -120+13-23
2y= -130=>y= -65
e) => -21+32+5y= 16+4y
5y-4y= 16+21-32
y= 5
bài 1
a)y-(-42-2y) = (-12) - 14 +2y
y +42 + 2y = -12 -14 +2y
3y + 42 = -26 +2y
y = -68
b)15-(-y+5)-5y=-(12+5y+2)
15+y-5-5y=-12-5y-2
10-4y=-14-5y
-4y+5y=-14-10=-24
c)2y-(-5+8y-21)=-3-(5y+2)
2y+5-8y+21=-3y-5y-2
-6y+26=-8y-2
-6y+8y=-2-26
2y=-28
y=-28/2=-14
=338,0867543
338,1 nha em